2017
DOI: 10.4103/ejd.ejd_202_16
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of mandibular condyles in patients with temporomandibular disorders and normal controls using cone beam computed tomography

Abstract: Objectives:The aim of the study is to investigate the condylar position and its relation to articular eminence and axial condylar angle in temporomandibular joint disorder (TMD) patients and in normal controls using cone beam computed tomography (CBCT).Materials and Methods:CBCT temporomandibular joint (TMJ) images of 70 participants (38 males and 32 females, mean age 26.4 years) were analyzed. They were divided into control group (including 35 subjects) and study group (including 35 subjects). Linear measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
5
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 26 publications
2
32
5
2
Order By: Relevance
“…They found the mean HCA of the males with healthy TMJs to be 23.18°, while the mean HCA of the males who had a temporomandibular disorder was found to be 18.36°. The mean HCA of the females with healthy TMJs was found to be 21.19°, while this value for the females with a temporomandibular disorder was 15.63° (11). In our study, there was no significant difference found between the HCAs of the male and female patients, although in the study by Al-Rawi et al there was a significant difference in favor of the males.…”
Section: Discussioncontrasting
confidence: 68%
“…They found the mean HCA of the males with healthy TMJs to be 23.18°, while the mean HCA of the males who had a temporomandibular disorder was found to be 18.36°. The mean HCA of the females with healthy TMJs was found to be 21.19°, while this value for the females with a temporomandibular disorder was 15.63° (11). In our study, there was no significant difference found between the HCAs of the male and female patients, although in the study by Al-Rawi et al there was a significant difference in favor of the males.…”
Section: Discussioncontrasting
confidence: 68%
“…CBCT is a cost-effective method that is being used with increasing frequency for the diagnosis of maxillofacial structures 14. Maxillofacial and oral radiologists should be familiar with the sino-nasal complex region.…”
Section: Discussionmentioning
confidence: 99%
“…[19] Mandibular condyle was classified into four types according to its shape as; convex, flat, angular and round. [20][21][22] The mandibular condyle was evaluated in the coronal PDW sequence in close mouth position ( Figure 4).…”
Section: Methodsmentioning
confidence: 99%